Autologous Chondrocyte Implantation in Physically Active Patients - A Narrative Review - Smagoń, Jakub; Rafalska, Izabela; Kaim, Martyna; Majewska, Melania; Piasecka, Natalia; Siewiera, Wiktoria; Bober, Joanna; Kornacka, Natalia; Bednarski, Krzysztof; Bochenek, Magdalena (Quality in Sport, 2026)
Background. Focal articular cartilage defects of the knee represent a significant clinical problem, particularly in physically active patients and individuals with high functional demands. These lesions are associated with pain, functional limitation, and an increased risk of early osteoarthritis. Due to the limited intrinsic healing capacity of hyaline cartilage, various reparative strategies have been developed, among which autologous chondrocyte implantation (ACI) is one of the most important cell-based techniques. Aim. The aim of this study was to summarize current evidence regarding the biological basis, surgical techniques, clinical effectiveness, patient selection, and rehabilitation of ACI, with particular emphasis on physically active individuals. Materials and Methods. This study was designed as a structured narrative review synthesizing literature on cartilage biology, pathophysiology of focal defects, classification systems, operative treatment options, and ACI and MACI techniques. Consideration was also given to biomaterials, clinical outcomes, complications, patient selection, and rehabilitation strategies in individuals with increased functional demands. Results. Available evidence indicates that ACI enables formation of repair tissue with properties more similar to hyaline cartilage compared with marrow stimulation techniques. This results in clinically meaningful improvement in pain and knee function, particularly in physically active patients. Compared with microfracture, ACI may provide more durable outcomes, although success depends on appropriate patient selection, correction of biomechanical abnormalities, and structured rehabilitation. Conclusions. ACI represents a valuable treatment option for physically active patients with focal knee cartilage defects, although it remains technically demanding and requires further optimization.